The apparent breastfeeding paradox in very preterm infants: relationship between breast feeding, early weight gain and neurodevelopment based on results from two cohorts, EPIPAGE and LIFT. Issue 2 (5th April 2012) - Rozé, Jean-Christophe; Darmaun, Dominique; Boquien, Clair-Yves; Flamant, Cyril; Picaud, Jean-Charles; Savagner, Christophe; Claris, Olivier; Lapillonne, Alexandre; Mitanchez, Delphine; Branger, Bernard; Simeoni, Umberto; Kaminski, Monique; et al.
Abstract : Context: Supplementation of breast milk is difficult once infants suckle the breast and is often discontinued at end of hospitalisation and after discharge. Thus, breastfed preterm infants are exposed to an increased risk of nutritional deficit with a possible consequence on neurodevelopmental outcome. Objective: To assess the relationship between breast feeding at time of discharge, weight gain during hospitalisation and neurodevelopmental outcome. Design: Observational cohort study. Setting: Two large, independent population-based cohorts of very preterm infants: the Loire Infant Follow-up Team (LIFT) and the EPIPAGE cohorts. Patients: 2925 very preterm infants alive at discharge. Main outcome measure: Suboptimal neurodevelopmental outcome, defined as a score in the lower tercile, using Age and Stages Questionnaire at 2 years in LIFT and Kaufman Assessment Battery for Children Test at 5 years in EPIPAGE. Two propensity scores for breast feeding at discharge, one for each cohort, were used to reduce bias. Results: Breast feeding at time of discharge concerned only 278/1733 (16%) infants in LIFT and 409/2163 (19%) infants in EPIPAGE cohort. Breast feeding is significantly associated with an increased risk of losing one weight Z-score during hospitalisation (LIFT: n=1463, adjusted odd ratio (aOR)=2.51 (95% CI 1.87 to 3.36); EPIPAGE: n=1417, aOR=1.55 (95% CI 1.14 to 2.12)) and with a decreased risk for a suboptimal neurodevelopmental assessment (LIFT: n=1463, aOR=0.63 (95% CI 0.45 to 0.87); EPIPAGE: n=1441, aOR=0.65 (95% CI 0.47 to 0.89) and an increased chance of having a head circumference Z-score higher than 0.5 at 2 years in LIFT cohort (n=1276, aOR=1.43 (95% CI 1.02 to 2.02)) and at 5 years in EPIPAGE cohort (n=1412, aOR=1.47 (95% CI 1.10 to 1.95)). Conclusions: The observed better neurodevelopment in spite of suboptimal initial weight gain could be termed the 'apparent breastfeeding paradox' in very preterm infants. Regardless of the mechanisms involved, the current data provide encouragement for the use of breast feeding in preterm infants.